TRACES OF LEAN CONSTRUCTION PRACTICES IN THE INDIGENOUS BUILDING CULTURE OF THE TALENSI OF NORTHERN GHANA - Zoya Evans KPAMMA; Eric Kwaku ASARE; Emmanuel Nsiah ANKOMAH (Journal of Construction Project Management and Innovation)
Lean construction (LC) is a project delivery system that focuses on delivering projects to meet the needs of clients while minimising waste. Even though a number of authors have indicated a strong link of LC to the Toyota Production System, there appear to be traces of LC in some indigenous building cultures. A closer study of the indigenous construction practices of the Talensi of Northern Ghana reveals traces of an LC philosophy. An attempt to establish an apparent link between the indigenous building culture of the Talensi and the concept of LC was carried out through field observations, interviews and a literature review. The study points to the fact that even though the term ‘lean construction’ might not have been coined by then, traces of LC as a culture, such as ensuring reliable flow, promoting collaboration, ensuring respect for people and improving transparency, were identifiable with the indigenous building culture of the Talensi. The outcome of this study should provide a basis to enhance the geographic spread of LC implementation by regenerating indigenous practices that identify with the lean concept.